A study of calmodulin binding to the alternatively spliced C-terminal domain of the plasma-membrane CA2-pump - Kessler, Félix; Falchetto, Rocco; Heim, Roger; Meili, Ruedi; Vorherr, Thomas; Strehler, Emanuel; Carafoli, Ernesto (My University, 1992)
The C-terminal regions of the four human plasma membrane Ca2+ pump isoforms 1a-d generated from alternatively spliced RNA have been expressed in Escherichia coli, and the recombinant proteins have been purified to a very high degree. The C-termini of isoforms 1a, 1c, and 1d contain an insert encoded by an alternatively spliced exon which is homologous to the calmodulin binding domain of isoform 1b. In isoforms 1c and 1d (29 and 38 amino acid insertions, respectively), subdomain A of the original calmodulin binding site of isoform 1b is followed by the spliced-in domain, which is then followed by subdomain B of the original calmodulin binding site. The positive charges of histidine residues at positions 27, 28, and 38 of the alternatively spliced sequence are likely to be responsible for the observed pH-dependent calmodulin binding to the novel "duplicated" binding site. The affinity of calmodulin for the C-terminal domains of isoforms 1a, 1c, and 1d, which contain the histidine-rich inserts, is much higher at pH 5.9 than at pH 7.2. A synthetic peptide (I31) containing 31 amino acids of the alternatively spliced sequence (from residue 9 to 40) also binds calmodulin with strong pH dependency. Alternative splicing in the C-terminal domain is proposed to confer pH dependence to the regulation of the activity of Ca2+ pump isoforms.
Keywords: CA-2+ PUMP; MOLECULAR-CLONING; ERYTHROCYTE CA-2+-ATPASE; SKELETAL-MUSCLE; CALCIUM-PUMP; CA-2+-TRANSPORTING ATPASE; PHOSPHORYLASE-KINASE; REGULATORY DOMAIN; SEQUENCE; IDENTIFICATION